Optical humidity sensing behaviour of sol–gel processed nanostructured ZnO films - Yadav, B.C.; Yadav, R.C.; Dubey, G. C. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
This paper reports the humidity sensing behaviour of sol–gel processed ZnO films deposited on U-shaped borosilicate rods as substitute of optical fiber having the same radius of curvature. The films prepared on each sensing element were dried for 15 minutes using a 100 watt electric bulb. Both ends of the U-shaped borosilicate rod were coupled to optical fibers. Light from a He-Ne laser is fed into the sensing element through one of the ends. Light is received from the other end of fiber coupled into an optical power meter. Variations in the intensity of light with changes in humidity from 10% to 95% have been recorded. Characterization of sensing material has been done using SEM.
Optica Applicata, Vol. 39, 2009, nr 3, s. 617-627
Keywords: optyka; humidity sensors; optical fiber; sol-gel dip process